Genetic diversity of two poleroviruses affecting faba bean and chickpea crops in Tunisia - Kumari, Safaa; Najar, Asma; Mghandef, Samia; Moukahel, Abdulrahman (International Center for Agricultural Research in the Dry Areas, 2023)
Faba bean (Vicia faba L.) is the most cultivated grain legume representing 70% of the total food legume planted area in Tunisia (Khamassi et al., 2021), followed by chickpea (Cicer arietinum L.). These crops offer an important and inexpensive source of high-quality protein in the diets and a valuable source of nutritious fodder for livestock. However, production levels of these crops remain quite low which is often attributed to abiotic and biotic stresses that are prevailing in the major growing areas. Viruses causing yellowing and stunting symptoms represent one of the major constraints that reduce the genetic potential of most cultivated species and varieties. Knowledge of genetic variation and the exact identity of viruses affecting crops is essential for breeding for resistance and effective crop management. Serological tests for more than 3000 faba bean and chickpea samples collected from different locations in Tunisia during 2013-2022, showed that the most important viruses are Chickpea chlorotic stunt virus (CpCSV) on both crops, and Beet western yellows virus (BWYV) on faba bean only. Both viruses are transmitted by aphids in the persistent manner. Representative samples were selected for further molecular analysis with RT-PCR followed by sequencing to study the genetic diversity and identify of these viruses at the molecular level.